Interaction of transforming growth factor β1 with human glomerular epithelial cells in culture: opposite effects on synthesis of matrix proteins and on urokinase plasminogen activator - Wagner, Christof; Viedt-Suelmann, Christiane; Bürger, Antje; Filsinger, Sabine; Kramer, Michael D.; Hänsch, Gertrud Maria (Journal of molecular medicine, 1996)
The effect of transforming growth factor-β (TGF-β) was analyzed on the synthesis of fibronectin, collagen type IV, and urokinase plasminogen activator in human glomerular epithelial cells in culture. An increase in the abundance of specific mRNA was found for collagen type IV and fibronectin. Fibronectin protein synthesis was also increased in TGF-β treated cells; most of the de novo synthesized fibronectin was found as an unsoluble protein associated with extracellular matrix. In the same cells the amount of plasminogen activator mRNA was found leading also to a decreased surface expression of urokinase plasminogen activator. The data support the concept that by upregulating matrix protein synthesis and downregulating the plasminogen activator system, TGF-β favors the development of sclerosis.